2010
DOI: 10.1111/j.1469-8749.2009.03464.x
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mass in patients with motor disability: prevalence and risk factors in 59 Finnish children

Abstract: aBMD Areal bone mineral density BMAD Bone mineral apparent density; DXA Dual-energy X-ray absorptiometry P-ALP Plasma alkaline phosphatase P-Ca Plasma calcium P-Crea Plasma creatinine P-Pi; Plasma phosphate P-PTH Plasma parathyroid hormone S-E2 Serum oestradiol S-FSH Serum follicle stimulating hormone S-LH Serum luteinizing hormone S-Testo Serum testosterone U-Crea Urine creatinine U-Ca Urine calcium S-25-OHD Serum 25-hydroxyvitamin D AIM Children with motor disabilities are at increased risk of compromised bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 40 publications
(81 reference statements)
1
19
0
Order By: Relevance
“…We have previously shown in several other cohorts that vitamin D deficiency is alarmingly common in all age groups in Finland (23,29,30,31,32). The findings in the present cohort are in line with these observations.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown in several other cohorts that vitamin D deficiency is alarmingly common in all age groups in Finland (23,29,30,31,32). The findings in the present cohort are in line with these observations.…”
Section: Discussionsupporting
confidence: 93%
“…73,84 As noted, some individuals with vertebral fractures are relatively asymptomatic, even in more advanced stages of collapse. 71 Therefore, to detect vertebral fractures, spine imaging should not be prompted solely by back pain or deformity; rather, people with known risk factors for vertebral fractures, including motor disorders 85 or glucocorticoid therapy, 72,84 should receive regular spine imaging. The fact that vertebral fractures at any time point in a patient’s clinical course are predictive of future spine fractures even when the initial vertebral fractures are mild or asymptomatic 71 —a phenomenon known as the vertebral fracture cascade 86 — underscores the need for early identification.…”
Section: Bone Health and Osteoporosis Managementmentioning
confidence: 99%
“…A pilot study demonstrated that 18 months of growth hormone therapy was associated with a statistically significant improvement in spinal BMD [38]. Although numerous studies such as these have investigated treatment of low BMD in children [3740], relatively few studies have included adults. Since vitamin D levels are essential for normal skeletal mineralization and bone metabolism, vitamin D status was evaluated in institutionalized adults with ID in an open label trial [41].…”
Section: Prevention and Treatment Of Low Bmd In Adults With D/idmentioning
confidence: 99%